OPTIMALISASI KINERJA UNIT TIPIDUM DALAM PROSES PENYIDIKAN TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN GUNA TERWUJUDNYA PROFESIONALITAS PENYIDIK DI WILAYAH HUKUM POLRES BATANG - HERIANSYAH HERIANSYAH (Police Studies Review, 2022)
ABSTRACT OPTIMIZING THE PERFORMANCE OF INVESTIGATORS IN THE PROCESS OF THE CRIMINAL ACT OF THEFT INVESTIGATION WITH WEIGHT FOR THE PROFESSIONALTY OF INVESTIGATORS IN THE JURISDICTION OF THE BATANG POLICE Heriansyah, 18.068, heri.ansyah51@gmail.com Theft by weight is a crime with the highest crime index at the Batang Polres from 2017-2021 and in the investigation process there are always cases of arrears every year. This study aims to describe the performance of investigators in the process of investigating criminal acts of theft with weights in order to realize the professionalism of investigators in the jurisdiction of the Batang Polres and to find out the efforts that have been made to optimize the performance of investigators in the process of investigating criminal acts of theft by weighting in order to realize the professionalism of investigators in the jurisdiction of the Batang Polres. The concepts and theories used are the Optimization Concept, the Investigator Concept, the Investigation Process Concept and the Professional Concept. Meanwhile, the theory is POAC management theory and organizational resource theory. The research method used is field research, qualitative approach and descriptive analysis type of research. Sources of data obtained from primary and secondary data. Meanwhile, to collect data using interview, observation, and document study methods. The research location is the Batang Resort Police Criminal Investigation Unit. The validity of the data uses triangulation of sources, techniques and time, as well as for data analysis using data reduction, data presentation and conclusions as well as data verification. The results obtained during the research are the lack of witnesses, no evidence has been found, the perpetrators of the theft are people outside Batang Regency, lack of personnel, the budget in the field is different from the specified budget, not all of the personnel of the Criminal Investigation Unit have qualified competence seen because they don’t have an Investigator's Decree, don’t yet have an investigator's certificate and most have not carried out education and vocational training and lack of facilities and infrastructure in the investigation. In conclusion, the implementation of the investigation process is in accordance with the Regulation of the Head of the National Police of the Republic of Indonesia Number 6 of 2019 concerning the investigation of criminal acts and the Regulations of the Head of the Criminal and Investigation Agency Numbers 1,2,3 and 4 concerning Standard Operating Procedures for the investigation of criminal acts, but have not run optimally